The City After Abandonment - Thomas, June Manning; Dewar, Margaret E. (Margaret Elizabeth), 1948- (Book collections on Project MUSE., 2013)
Looking at the shrinking cities of the Midwest and Northeast as well as New Orleans, urban planning experts examine the conditions of disinvested places and lay out ways policymakers and planners can approach the future through processes and ideas that differ from those applicable to growing cities.